Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations 36 HEALTH AND CLEANLINESS on a very cold morning, for instance, the class may be asked, "Which of you slept with open windows last night?" If the teacher cares to centre his talks about cleanliness around the pioneer's life in the cabin, the seaman's life on board ship, the castaway's life in the log hut, he will discover that boys can be as interested in the cleanliness of domestic interiors as girls may be. A great deal of the lesson material here dealt with will [Image with caption: There is a class of people dears Whose failing makes me scowl Instead of washing clean their hands They wipe them on the towel!] Reproduction of postcard (L. 42) issued by the Health and Cleanliness Council in various colours. be taken in the ordinary way with girls in the course of training in housecraft. But the work at this later stage will benefit greatly if the children have acquired, through lessons and discussions at an earlier stage, a proper attitude towards cleanliness, an appreciation of the efforts made to secure it, and a willingness to co-operate in the making of such efforts. Their experience in the classroom, 177/5/8/3